PERANCANGAN STRUKTUR HOTEL IBIS BUDGET SEMARANG - Ramadhianto, Wirajati; Puspitarini, Novia; Nurhuda, Ilham; Nuroji, Nuroji (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Structural Design of Ibis Budget Hotel Semarang was designed to comply with SNI 2847-2013 and SNI 1726-2012. Seismic analysis was conducted using dynamic respons spectrum method. The building was designed to be located in zone 4 Indonesian seismic vurnability map meaning that it can experience large earthquake acceleration. Hence the building must be designed as an earthquake-resistant structures. This building was designed as special moment resisting frame systems (SMRFS). The frame system was composed of beams and columns. The columns were designed to be stronger than the beams (strong column-weak beam concept). The concrete was of f'c 29,05 MPa, and the steel reinforcement of the longitudinal bar was fy 400 MPa. The Structure analysis was conducted using an analysis structure program to model the structure and calculate the internal forces on the structure. Failure at the beam-column joint was avoided by designing plastic hinges to occur at the beam ends and at the top base columns connected to foundation.